Maternal Health Care Service Utilization and Its Role in Postpartum Family Planning Use in Nepal - Dulal, Momal Prasad (Journal of Management and Development Studies, 2015)
Family planning and maternal health care programme has been initiated in an integrated approach for a long time in Nepal. However, the use status of family planning method could not be presented at good instance. The International Conference on Population and Development (ICPD), 1994 and later millennium development goal 2002, both paved the way out for the situation mostly in the developing countries. Nepal also has made some changes in its services aiming to reduce high maternal mortality and promote to use family planning method. Use of family planning method within 12 months after childbirth could be a right solution for many developing countries like Nepal having high unintended birth. Therefore, this paper aims to analyse the role of maternal health care service utilization in initiating use of family planning method after post-partum period. Women’s data file from Nepal Demographic Health Survey, 2011 has been used for the analysis. Bivariate and multivariate analysis result have revealed that the role of delivery care, controlling other variables seems to be much appreciable in getting family planning use within 12 months of delivery. Effects of some study variables besides delivery care remains unchanged in different models. Therefore, embracing family planning programme along with maternity care components would have implications towards - increasing current use of family planning, reducing the chances of unwanted/unintended birth, providing opportunities to control over female own body, contribution in achieving replacement level fertility and maintaining good health for both mother and the baby.